Kerangka Hukum dan Perkembangan Asuransi Syariah di Indonesia - Mardani; Yessy Kusumadewi; Sidauruk, Averin Dian (Islam & Contemporary Issues, 2025)
This article aims to analyze the development of Islamic insurance (takaful) in Indonesia from a regulatory and institutional perspective since its inception in 1994. The study focuses on the evolution of legal frameworks governing Islamic insurance, the growth trajectory of Islamic insurance companies, and the development of their assets over time. Using a normative juridical approach, the research examines relevant statutory regulations, fatwas, and institutional policies to assess the extent to which the legal infrastructure has supported or constrained the progress of Islamic insurance in Indonesia. The findings indicate that while Islamic insurance has shown steady development, particularly in terms of asset accumulation and institutional expansion, its growth remains relatively limited when compared to the more advanced Islamic banking sector. Several regulatory and structural challenges, such as inconsistencies in legislation, lack of public awareness, and limited product innovation, continue to impede the sector's full potential. This article contributes to the academic discourse on Islamic insurance law by providing a comprehensive legal analysis of its development in Indonesia and identifying critical regulatory gaps that need to be addressed. The study proposes the need for regulatory reform to harmonize existing laws and strengthen institutional support mechanisms. In doing so, it aims to enrich the literature on Islamic insurance and offer practical recommendations for policymakers to enhance the legal and operational environment of the takaful industry in Indonesia.